Gasto obscura : a food adventurer's guide - Wong, Cecily; Thuras, Dylan; Rummel, Rachel; Ewbank, Anne; O'Brien, Sam (Workman Publishing, 2021)
"Taste the World! It's truly a feast of wonder: Created by the ever-curious minds behind Atlas Obscura, this breathtaking guide transforms our sense of what people around the world eat and drink. Covering all seven continents, Gastro Obscura serves up a loaded plate of incredible ingredients, food adventures, and edible wonders. Ready for a beer made from fog in Chile? Sardinia's "Threads of God" pasta? Egypt's 2000-year-old egg ovens? But far more than a menu of curious minds delicacies and unexpected dishes, Gastro Obscura reveals food's central place in our lives as well as our bellies, touching on history-trace the network of ancient Roman fish sauce factories. Culture-picture four million women gathering to make rice pudding. Travel-scale China's sacred Mount Hua to reach a tea house. Festivals-feed wild macaques pyramid of fruit at Thailand's Monkey Buffet Festival. And hidden gems that might be right around the corner, like the vending machine in Texas dispensing full sized pecan pies. Dig in and feed your sense of wonder. "Like a great tapas meal, Gastro Obscura is deep yet snackable, and full of surprises. This is the book for anyone interested in eating, adventure and the human condition." -Tom Colicchio, chef and activist "This exquisite guide kept me at the breakfast table until dinner time." -Kyle Maclachlan, actor and vintner"--